Vespa Motorcycle Lighting Modification Using AHP System With Fullwave Ignition - Bella Cornelia Tjiptady; Indah Martha Fitriani; Rifki Zainur Rahman; Muhammad Rizal Akbar Zamzami; Muhammad Ana Zamzami; Kiki Darmawan (G-Tech: Jurnal Teknologi Terapan, 2024)
This study focuses on the modification of Vespa motorbike lighting by implementing the Aho system with Fullwave charging. The process involves replacing the regulator cable line with a Honda Tiger regulator to convert the AC lighting system to full wave. Additionally, the upgrade includes replacing the halfwave regulator with a fullwave kiprok type using 4 diode bridges to convert AC to DC current efficiently. LED lamps are also substituted for their energy efficiency and optimal performance with DC current. The research emphasizes the importance of enhancing lighting systems for motorcycle safety and compliance with traffic regulations. The findings highlight the benefits of these modifications in improving lighting efficiency and overall safety for Vespa motorbike users.